2020
DOI: 10.1371/journal.pone.0230153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthetic fertilizer and farm compost on soil nematode community in long-term crop rotation plots: A morphological and metabarcoding approach

Abstract: Soil biodiversity plays a key regulation role in the ecosystem services that underpin regenerative sustainable agriculture. It can be impacted by agricultural management techniques, both positively (through measures such as compost application) and negatively (through, for example, application of synthetic nitrogen). As one of the most numerous members of the soil biota, nematodes are well established as indicators for the soil food web. However, compost application also includes the addition of nematodes pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Approximately nine variable regions of eukaryotic SSU genes have been suggested as potential DNA barcodes by Hugerth et al [ 38 ] and Hadziavdic et al [ 37 ]; several metabarcoding studies of isolated terrestrial nematode communities have been reported. In many of these, the V7–V8 region (region 4 in this study) of the SSU gene amplified by the primer set including NF1 and 18Sr2b has been preferentially used as a DNA barcode [ 20 , 22 , 30 33 , 36 , 56 ] ( S1 Fig ). The V1–V2 (here, region 1) [ 36 ], V4–V5 (here, region 2) [ 21 , 32 , 57 , 58 ], and V9 [ 58 ] regions have also been used for DNA barcoding of nematodes ( S1 Fig ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately nine variable regions of eukaryotic SSU genes have been suggested as potential DNA barcodes by Hugerth et al [ 38 ] and Hadziavdic et al [ 37 ]; several metabarcoding studies of isolated terrestrial nematode communities have been reported. In many of these, the V7–V8 region (region 4 in this study) of the SSU gene amplified by the primer set including NF1 and 18Sr2b has been preferentially used as a DNA barcode [ 20 , 22 , 30 33 , 36 , 56 ] ( S1 Fig ). The V1–V2 (here, region 1) [ 36 ], V4–V5 (here, region 2) [ 21 , 32 , 57 , 58 ], and V9 [ 58 ] regions have also been used for DNA barcoding of nematodes ( S1 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of taxonomic analyses of nematodes in forest [ 33 , 58 , 60 71 ] and agricultural field [ 11 , 13 , 15 17 , 19 22 , 30 , 72 ] soils. Studies on forest soils have shown that bacteria, plant, and fungus feeders occupy significant fractions of the nematode communities despite varied proportions by the sampling sites, periods, and environmental status of forests [ 33 , 62 , 68 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nematodes play crucial roles in the nutrient cycling of soil biota and influence plant growth [4,5]. Nematode taxonomic compositions vary by ecosystem type [6] and are influenced by various factors such as food, temperature, humidity, pH and nutrients in soils [7], soil properties [7,8], cultivated plants [9], tillage [10], and fertilizers [11,12]. These characteristics strongly indicate that the taxonomic composition of nematodes can be used as an excellent indicator for assessing biological, chemical, and nutrient status in soils [13,14].…”
Section: Introductionmentioning
confidence: 99%